Facial Nerve Preservation and Surgical Outcomes of Retrosigmoid Approach to Large Vestibular Schwannoma- an Eight-year Single Institution Experience - Shrestha, Pratyush; Kutu, Nisha; Lohani, Subash; Devkota, Upendra Prasad (Nepal Journal of Neuroscience, 2017)
Objective: To evaluate the result of microsurgical excision of vestibular schwannoma by retrosigmoid approach and to correlate the facial nerve outcome with the tumor size. Methods: Retrospective analysis of 84 patients with cerebello-pontine angle lesions (57 vestibular schwannomas) operated at National Institute of Neurological and Allied Sciences, Nepal, from Baisakh 2066 to Chaitra 2073 (eight years). Facial nerve outcomes as per the House and Brackmann grading at six months follow-up were recorded and correlated with tumor size. Result: The mean tumor size was 4.32 ± 1.23 cms and 48 (84.2%) of the patients had tumor size more than 3 cms. Patients presented late with papilloedema documented in 42.1% and preoperative ventriculoperitoneal shunting required in 31.57% patients. Of the patients whose facial nerve functions could be followed up, all patients with tumors < 3cm diameter had good House and Brackmann facial nerve outcome (grade I to III). Larger tumors had poorer facial nerve outcomes; however statistical significance could not be reached. (Fischer Exact test, p-value: 0.077). There were two mortalities (3.5%), one following cavity rebleed and one following malignant brain swelling. Conclusion: Retrosigmoid approach is a versatile surgical corridor to excise large vestibular schwannomas with minimal complications and larger tumors have poorer facial nerve outcomes. Nepal Journal of Neuroscience, Volume 14, Number 3, 2017, Page: 19-25